Soil Resource Inventory and Land Use Planning for Mandhala Watershed in Shiwalik Hills of North-West Himalayas using Remote Sensing and GIS - Sanjeev K. Chaudhary, J.C. Sharma and (Journal of the Indian Society of Soil Science, 2021)
Land resource mapping of Mandhala watershed representing Shiwalik hills of North-West Himalayas in Himachal Pradesh was done using multi-temporal and multi-spectral high resolution Indian remote sensing (IRS) satellite imagery and Survey of India (SOI) toposheets in conjunction with ground checks/field surveys to generate database layers including watershed boundary, drainage network, slope, landforms, land use/land cover, soils, land capability, suitability for major crops, suggested land use, etc. at 1:12,500 scale. About 55% of the watershed is under forests. Agriculture occupies about 12% area while rest is mainly under scrub and grasslands. These soils, still in initial stage of their pedogenic development, possess low productivity owing to inherent limitations related to topography, soil characteristics, erosion and erratic rainfall apart from excessive human interference. A need based resource conservation and land use plan consistent with the problems and potentialities identified in the area, was suggested by integrating different database layers in geographical information system (GIS) environment. The study also demonstrated utility of remote sensing (RS) and GIS techniques in sustainable natural resource development planning.